Pengetahuan Wajib Pajak, Pemahaman Wajib Pajak, Kesadaran Wajib Pajak dan Pelayanan Fiskus terhadap Kepatuhan Wajib Pajak - Mahfuzza Dinda Hadi; Dimas Wahyu Hadi Prasetyo; Thomas Firdauz Hutahaean (IPM2KPE, 2022)
The purpose of the study was to analyze tax knowledge, understanding of taxpayers (WP), taxpayer awareness (WP), and tax service services on taxpayer compliance (WP). This research method is descriptive quantitative. The data analysis technique is multiple linear regression and classical assumptions. The results showed, the results of the T test showed, a) knowledge of taxpayers has a value of tcount = -1.410 at sig.0.162; b) understanding of taxpayers has a value of tcount = 4.869 at sig.0.000; c) awareness of WP value tcount = 3.383 at sig.0.002; d) Fiscal Service has a value of tcount = 1.611 at sig.0.111. There is a very strong correlation between the independent and dependent variables (value of R square = 0.771), and the magnitude of the percentage is 48.4% and the remaining 51.6% can be explained by other variables outside the scope of research that were not carried out. In conclusion, the partial test of the independent variables, namely tax knowledge and tax service services, has no effect on taxpayer compliance, while the variable understanding of taxpayers and taxpayer awareness has an effect on taxpayer compliance variables. Simultaneously, all independent variables, namely tax knowledge, taxpayer understanding (WP), taxpayer awareness (WP), and tax service services have a significant effect on the dependent variable, namely taxpayer compliance. Keywords: Taxpayer Compliance, Taxpayer Awareness, Fiscus Service, Taxpayer Understanding, Tax Knowledge The purpose of the study was to analyze tax knowledge, understanding of taxpayers (WP), taxpayer awareness (WP), and tax service services on taxpayer compliance (WP). This research method is descriptive quantitative. The data analysis technique is multiple linear regression and classical assumptions. The results showed, the results of the T test showed, a) knowledge of taxpayers has a value of tcount = -1.410 at sig.0.162; b) understanding of taxpayers has a value of tcount = 4.869 at sig.0.000; c) awareness of WP value tcount = 3.383 at sig.0.002; d) Fiscal Service has a value of tcount = 1.611 at sig.0.111. There is a very strong correlation between the independent and dependent variables (value of R square = 0.771), and the magnitude of the percentage is 48.4% and the remaining 51.6% can be explained by other variables outside the scope of research that were not carried out. In conclusion, the partial test of the independent variables, namely tax knowledge and tax service services, has no effect on taxpayer compliance, while the variable understanding of taxpayers and taxpayer awareness has an effect on taxpayer compliance variables. Simultaneously, all independent variables, namely tax knowledge, taxpayer understanding (WP), taxpayer awareness (WP), and tax service services have a significant effect on the dependent variable, namely taxpayer compliance. Keywords: Taxpayer Compliance, Taxpayer Awareness, Fiscus Service, Taxpayer Understanding, Tax Knowledge